Building information modeling and building performance simulation interoperability: State-of-the-art and trends in current literature. (October 2022) - Di Biccari, Carla; Calcerano, Filippo; D'Uffizi, Francesca; Esposito, Antonio; Campari, Massimo; Gigliarelli, Elena
Highlights: Review of the state-of-the-art of BIM and BPS integration and interoperability using a Systematic Literature Review and an expert review of relevant sources of knowledge. Exploration of strategies for interoperability, main characteristics of information transfer pipelines and related issues reported in the literature. Review of Research Projects funded by the European Union and Guidelines for BIM and BPS interoperability. Discussion of the main trends emerged from the review and indication of possible future research developments. Abstract: The study outlines the state-of-art on interoperability between Building Information Modeling (BIM) and Building Performance Simulation (BPS). First, the paper organises the result of a Systematic Literature Review (SLR) on the topic into three main strategies to achieve interoperability: the scripting to automate the information transfer between BIM and BPS environments, the pipelines supported by current practices, and the MVD and IFC schema extension approach. Software applications, types of files involved, building features, life cycle phases and model geometry considered by the literature along with reported interoperability issues, are also analysed. Secondly, an expert review of grey literature focusing on EU funded projects, guidelines, reports, best practices and key initiatives on the field of BIM to BPS interoperability is presented. The study wraps up by reporting on six major research trends identified by the review and highlighting future developments. The results of the review seem to indicate that effective interoperability can be achieved with the definition of a commonly accepted strategy, integrating shared guidelines for modelling, a better inclusion of energy evaluations through the whole life cycle of a building and the upgrade of software application for the accurate production of information with open format exchange files.